Peningkatan Keterampilan Kader Posyandu dalam Pengukuran Antropometri di Desa Meteseh, Boja, Kendal - Puji Lestari; Wenny Dwi Kurniati; Anisa Herdin Hidayati (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Meteseh Village is a village with 8 Posyandu. Various posyandu activities have been carried out, one of the routine activities carried out is anthropometric measurements, but there are still cadres who take measurements in an inappropriate way. This can produce erroneous measurement results, resulting in inaccurate interpretation. The accuracy of anthropometric measurements depends on the ability of cadres to make measurements, so training and assistance is needed in anthropometric measurements with the aim of increasing the knowledge and abilities of cadres in taking anthropometric measurements. The methods used in training and mentoring anthropometric measurements are lecture, discussion, simulation and demonstration methods using Ms. Power Point and various anthropometric measurement tools. Assistance is carried out within two months. Measurement of knowledge is done by giving pre-test and post-test. The activity was carried out with 50 Meteseh Village cadres, Boja, Kendal from June to September 2022. Based on the results of the pre-test and post-test, 60% of the cadres experienced an increase in knowledge. The results of the observations during the mentoring and evaluation of the participants also showed good results in the training and mentoring activities. suggestions that training and mentoring can be carried out on an ongoing basis to refresh the knowledge and consistency of cadres in making anthropometric measurements.